Simulated malingering on binomial forced-choice digit memory test – using eye movements to understand faking cognition impairment process. Issue 6 (2nd November 2021) - Zhong, Shaoling; Liang, Xiaoxi; Wang, Jun; Mellsop, Graham; Zhou, Jiansong; Wang, Xiaoping
ABSTRACT: Intentional faking and/or exaggeration of disability increase unnecessary burden and costs for society, and they could be difficult to detect. This study aimed to explore which and how eye-based measures could be applied in detecting malingering of traumatic brain injury in a laboratory setting. Undergraduates were randomly grouped into two conditions in a mixed study-design experiment: malingering (n = 25) and honest (n = 24). Binomial forced-choice digit memory test (BFDMT) was used to test performance validity. Behavioral and eye-based measures were collected. Compared to the honest individuals, the malingering participants exhibited longer dwell time, glance duration, and fixation time and more glance count and fixation count in false response while less dwell, glance, and fixations in true response. Individuals coached to malinger had more dwell, glance, and fixations in false than in true response. Findings suggested that gaze pattern may have a potential application in understanding the faking process and detecting malingering. In addition, individuals that were incentivized to malinger allocated intensive attention to desirable information as a strategy to avoid detection and maximize gains in this simulated setting.